Evaluación clínica y radiografía de autotrasplantes y reposiciones dentales 1994-1997 - Naranjo-Restrepo, Rodrigo Felipe; Ordóñez-D., Dora Eugenia; Díaz-Logreira, Francisco J. (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Fifteen autotransplanls and two dental repositions were prospectively evaluated. The patients, who have consulted since august of 1994 to april of 1997, were recruitedfrom the Stomatology Unit of San Vicenl Hospilal. The follow up of these patients was held for a period of one year. The following clinical and radiographic parameters were evaluated: Pain, color change, bleeding, morbility, space of periodontal ligament, internal and external ressorption, obliteration of the pulp chamber and stage of radicular development. There were various donar teeth and different receptor siles. The most frequent autotransplant was done using third molars to replace first molar teeth. The repositions were done in the premolar area. The survival rate was 100% al six months and 75% al twelve months. And they lasted 24 months. One of the autotrasplants was lost despite the pulp treatment done with calcium hydroxide. The initial result in this pilot study is that autotrasplants and dental repositions are importanl treatment alternatives with a high percentage of success, in patients with tooth decay or alteration in the eruption by malpositions.